2009
DOI: 10.2147/dddt.s3868
|View full text |Cite
|
Sign up to set email alerts
|

Selective reversal of muscle relaxation in general anesthesia: focus on sugammadex

Abstract: Despite the significant improvements in the pharmacology of muscle relaxants in the past six decades, the search for the ideal muscle relaxant continues, mainly because of the incomplete efficacy and persistent side effects associated with their antagonism. Clinical concerns remain about the residual paralysis and hemodynamic side effects associated with the classic pharmacologic reversal agents, the acetylcholinesterase inhibitors. Although the development of the "ideal muscle relaxant" remains illusory, phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Sugammadex is a synthetic γ‐cyclodextrin and the first member of the SRBA (selective relaxant binding agents) class of neuromuscular reversal medicines. Cyclodextrins are cyclic dextrose units that are linked together by 1–4 glycosyl bonds and are made from starch or starch derivates utilizing cyclodextrin glycosyltransferase [17]. Cortical neurons are protected from glutamate excitotoxicity and oxygen–glucose deprivation by a variety of cyclodextrin groups [18].…”
Section: Discussionmentioning
confidence: 99%
“…Sugammadex is a synthetic γ‐cyclodextrin and the first member of the SRBA (selective relaxant binding agents) class of neuromuscular reversal medicines. Cyclodextrins are cyclic dextrose units that are linked together by 1–4 glycosyl bonds and are made from starch or starch derivates utilizing cyclodextrin glycosyltransferase [17]. Cortical neurons are protected from glutamate excitotoxicity and oxygen–glucose deprivation by a variety of cyclodextrin groups [18].…”
Section: Discussionmentioning
confidence: 99%
“…The limited number of studies have reported that sugammadex does not have any clinically significant effect on blood pressure, heart rate, respiration, and thermoregulation. 14,15 There are only a few case presentations that show coronary vasospasm may be correlated with sugammadex. 16,17 The study, in which the hemodynamic effects of sugammadex and neostigmine on cardiac patients are compared, has found that sugammadex is more stable regarding cardiac function but causes a significant decrease in heart rate within the first minute after its administration.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its mechanism of action, sugammadex is thought to provide a faster and more predictable reversal of block. In addition, it can also avoid the unwanted side effects of neostigmine and antimuscarinic drugs (11)(12)(13). Sugammadex also does not affect heart rate, blood pressure, respiration, or thermoregulation in healthy patients (14).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it can also avoid the unwanted side effects of neostigmine and antimuscarinic drugs ( 11 13 ). Sugammadex also does not affect heart rate, blood pressure, respiration, or thermoregulation in healthy patients ( 14 ).…”
Section: Introductionmentioning
confidence: 99%